2012
DOI: 10.1371/journal.pone.0047325
|View full text |Cite
|
Sign up to set email alerts
|

The Pro Allele of the p53 Codon 72 Polymorphism Is Associated with Decreased Intratumoral Expression of BAX and p21, and Increased Breast Cancer Risk

Abstract: BackgroundThe TP53 Arg72Pro polymorphism encodes two p53 variants with different biochemical properties. Here we investigated the impact of this polymorphism on the expression of key p53 target genes in a panel of human breast carcinomas, breast cancer risk, and age at onset.Methodology/Principal FindingsThe Arg72Pro polymorphism was genotyped in 270 breast cancer patients and 221 control subjects. In addition, the Arg72Pro genotype of 116 breast tumors was determined, and correlated with intratumoral mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 49 publications
3
50
0
2
Order By: Relevance
“…These results are in agreement with several previous studies, which have reported an increased BC risk in association with Pro/Pro homozygous genotype [21][22][23][24][25][26][27][28]. Similarly, Tp53 Pro allele has been found to be associated with BC risk in North Indian [23], Austrian [22], Bangladeshi [28], Iranian [21], Turkish [30], Spanish [32], Swedish [26], American [34], German [33], Russian [36], Japanese [25], and Slovakian [35] populations.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with several previous studies, which have reported an increased BC risk in association with Pro/Pro homozygous genotype [21][22][23][24][25][26][27][28]. Similarly, Tp53 Pro allele has been found to be associated with BC risk in North Indian [23], Austrian [22], Bangladeshi [28], Iranian [21], Turkish [30], Spanish [32], Swedish [26], American [34], German [33], Russian [36], Japanese [25], and Slovakian [35] populations.…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, we investigated this single nucleotide polymorphism (SNP) in mammary carcinoma. Proestling et al (2012) showed that the p53 protein produced by the Arg-encoding allele appears to be a more potent transcription factor and tumor suppressor in vivo in human BC than the protein produced by the Pro-encoding allele. It has been suggested that the mechanism by which the codon 72 polymorphism increases apoptosis is the enhanced mitochondrial localization of p53 protein in cells with the Arg/Arg genotype; in contrast, the homozygous Pro (Pro/Pro) genotype induces higher levels of G1 arrest compared with the Arg/Arg genotype (Bišof et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When TP53 is mutated, this effect may be lost, resulting in uncontrolled cell proliferation that may result in tumorigenesis (16). It has been proposed that genetic polymorphisms in TP53 may affect a number of its functions (41).…”
Section: Patient Characteristicsmentioning
confidence: 99%